2001
DOI: 10.1046/j.1365-2559.2001.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid carcinoma of the colon arising at the splenic flexure

Abstract: Outside the anal canal, it has been postulated that basaloid colonic carcinomas may arise from cloacogenic embryologic rests, squamous metaplastic epithelium, or totipotential basal cells. The location and pathological findings of this tumour suggest that this rare colonic neoplasm arises from a totipotential basal cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15] Some of these histological types are associated with a worse prognosis than that of conventional adenocarcinoma. [16][17][18][19] To the best of our knowledge, there has only been one previously published report of micropapillary colorectal carcinoma by Kim et al 6 with a series from South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Some of these histological types are associated with a worse prognosis than that of conventional adenocarcinoma. [16][17][18][19] To the best of our knowledge, there has only been one previously published report of micropapillary colorectal carcinoma by Kim et al 6 with a series from South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…KJ Newell, J L Penswick and DK Driman states that basaloid carcinoma is the common neoplasm of the anorectal region. 11 In our study, there was only one case of carcinoid comprising of 0.46% of all microscopic types. Cullen PK states that 5 to 10% of carcinoid was located in the colon, with the majority occurring in the caecum.…”
Section: Sitementioning
confidence: 46%
“…As regards the basaloid variety of squamous cell carcinoma outside the anal canal, it may arise from cloaco- genic embryologic nests, squamous metaplastic epithelium, or totipotential basal cells [12]. In mixed adenosquamous variety, Cerezo and others suggested that all such lesions be carefully evaluated by means of immunoperoxidase stains and/or electron microscopy in order to identify squamous features [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, this rare histologic subtype of squamous cancer has been diagnosed in 3 patients with colorectal tumors, none more proximally than the splenic flexure [12]. Herein we present a case of a basaloid carcinoma of the rectum outside the anal canal, with a comprehensive review of the literature and a clarification of the clinicopathologic features of this rare entity.…”
Section: Introductionmentioning
confidence: 91%